Analysis of television consumption patterns and its impact on the state information policy of the Republic of Kazakhstan - Aidarkozhin, М.А.; Abdullin, Р.Б. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
In recent years, Kazakhstan has seen significant changes in media consumption of television. The study of television content patterns and their impact on the state information policy of the Republic of Kazakhstan is an important aspect of regional studies, since television broadcasting, due to its wide prevalence, plays a key role in shaping public opinion and cultural identity. This article presents an analysis of trends in the Kazakhstani television space. The study includes an analysis of audience indicators of the most popular Kazakhstani and foreign TV channels, providing statistical data as evidence of how popular this or that content is in terms of the genre orientation of TV programs, the age and gender structure of the population and regional divisions of the country. The purpose of this study is to identify trends and changes in television content consumption in Kazakhstan, as well as to assess their impact on the state information policy. In particular, the study focuses on the analysis of the dynamics of TV channel viewability, changes in audience preferences by age and gender groups, as well as genre preferences. Particular attention is paid to the issue of competitiveness of domestic content in comparison with foreign content. In this context, this issue is considered from the point of view of ensuring the country's information security. This study not only summarizes data on the television preferences of Kazakhstanis, but also offers practical recommendations for the further development of state information policy aimed at supporting domestic content and forming a positive public opinion.